Effect of Oxidized Wood Pulp Fibers on the Performance of the Thermoplastic Corn Starch Composites - Peng Yin; Wen Zhou; Xin Dong; Bin Guo; Yanan Huang (Advances in Polymer Technology)
In this study, oxidized wood pulp fiber (OWPF) was prepared by oxidizing wood pulp fiber (WPF) with NaIO4, and OWPFs with different oxidation degrees were obtained and characterized by light microscope, XRD, and TG. Then, OWPFs with different oxidation degrees were incorporated into thermoplastic starch (TPS) to prepare OWPF/TPS composites. The cross-section morphology, water resistance, and physical and mechanical properties of the composites were investigated. SEM showed good dispersion of OWPF in the continuous TPS phase. The tensile strength of OWPF/TPS reached a maximum value of 5.02 MPa when the oxidation degree of OWPF was 0.5. Elongation at break of OWPF/TPS composites increased with the increasing oxidation degree of OWPF. Meanwhile, as a result of cross-linking, the water contact angle was also improved with the increased oxidation degree of OWPF. The study provided a new way to prepare a degradable TPS composite with satisfying properties to be used for packaging and catering.